Co-Administration of CpG Oligonucleotides and Chenopodium album Extract Reverse IgG2a/IgG1 Ratios and Increase IFN-Gamma and IL-10 Productions in a Murine Model of Asthma - Tahereh Mousavi (Iranian Journal of Allergy, Asthma and Immunology, 2008)
Asthma is a disorder of increasing severity and prevalence. Recent knowledge about the pathogenesis of asthma emphasizes its inflammatory nature. CpG oligonucleotides are a class of compounds containing motifs based on the cytosine-guanine dinucleotides (CpG-ODNs). These motifs are suppressed in mammalian DNA. They induce inflammation in mammals characterized by the induction of T helper type 1 and regulatory responses.